Overview of Using Instagram as a Marketing Media of Apotek X Sleman - Manise, Chyntia Clarisa; Soegiantoro, Didiek Hardiyanto; Yuhara, Novena Adi (Sean Institute, 2025)
The development of digital technology has encouraged business actors, including pharmacies, to utilize social media as an effective marketing tool. Instagram, as a visual platform with a large number of active users, offers great potential in building interactions with consumers, increasing brand awareness, and expanding the reach of service and product information. This study aims to describe how Apotek X Sleman utilizes Instagram as a marketing medium throughout 2024, as well as identifying the types of content posted, audience responses, and potential strategies that can be optimized. This study uses a quantitative descriptive method with direct observation techniques on the official Instagram account of Apotek X. The data collected includes the number and type of content posted each month, user interactions in the form of likes and comments, and grouping comments based on sentiment (positive, negative, neutral) and question form. The data were analysed using Microsoft Excel to present a numerical and visual picture of the pharmacy's digital marketing activities. The results of the study show that during the period from January to December 2024, Apotek X published 227 original content without reposts from external parties, with the dominant content being drug information. This type of content also received the most responses from users, reaching more than 1,400 responses. No negative comments or complaints were found on all the content analysed. The highest spike in interactions occurred in June, which was likely triggered by promotional content or relevant health issues at that time. In conclusion, the use of Instagram by Apotek X has proven to be quite effective in building audience engagement and maintaining a positive image of the pharmacy. The development of relevant, educational, and trending content has proven to play an important role in increasing the effectiveness of the pharmacy's digital marketing strategy.